Chitosan-Based Zaleplon Nasal Microparticles - Sakhare, Sfurti S. (Asian Journal of Pharmaceutics (AJP), 2017)
Objectives: The purpose of present research work was to develop mucoadhesive microparticles of Zaleplon for nasal delivery with the aim to avoid hepatic first-pass metabolism, improve therapeutic efficacy and enhance residence time in the treatment of insomnia. Materials and Methods: Chitosan-based microparticles were prepared by the coacervation method by varying the drug:polymer ratio. The microparticles were evaluated for particle size and shape and surface morphology by scanning electron microscopy, drug content, drug entrapment efficiency, swelling study, in vitro mucoadhesion, differential scanning calorimetric (DSC), X-ray diffraction (XRD), Fourier transform infrared (FTIR), in vitro drug release study, and ex vivo drug permeation. Results: Zaleplon microparticles showed irregular-shaped particles and particle size was found to be in the range of 4.97â€“10.6 Î¼m, which is favorable for intranasal absorption. The prepared microparticles exhibited a good swelling index. The percentage drug content and entrapment efficiency was found to be in the range between 36.36% - 80% and 37.65% - 52.88%, respectively. In vitro mucoadhesion was performed by adhesion number using goat nasal mucosa and was observed in a range from 43.33 Â± 4.409 to 75 Â± 2.886%. It was observed that polymer concentration enhancement led to increased mucoadhesive strength. The results of DSC and XRD studies revealed the molecular amorphous dispersion of Zaleplon into the chitosan microparticles. IR spectra of Zaleplon along with excipient showed no interaction between Zaleplon and excipients. In vitro drug release from all the formulations was biphasic, being characterized by a slight â€œburstâ€ followed by slow release. At the end of 12 h, F6 (1:6) showed drug release of 81.66 Â± 1.545%, indicating sustained release. The permeation data of formulation from goat nasal mucosa was found near to that obtained with dialysis membrane in vitro. Conclusion: According to the obtained results, Zaleplon loaded chitosan microparticles prepared by coacervation method proved to be capable of sustained release and could be used through nasal route as an alternative to oral administration.